2015
DOI: 10.1590/1809-6891v16i131282
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição Espaço-Temporal Dos Diagnósticos Laboratoriais Da Raiva Animal

Abstract: Resumo:A raiva é uma enfermidade infectocontagiosa que afeta mamíferos, inclusive o homem. Estima-se que a raiva dos herbívoros seja responsável por enormes prejuízos econômicos na América Latina. O morcego hematófago Desmodus rotundus é o principal transmissor do vírus rábico (VR). Este estudo teve como objetivo avaliar a evolução do diagnóstico laboratorial para raiva animal em cinco espécies animais, na série cronológica 1990-2010, na microrregião Quirinópolis, Goiás, Brasil. Para avaliação da distribuição … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
5
0
4
Order By: Relevance
“…Some studies have reported the difficulty of finding hematophagous bats with RABV brain infections or even with least clinical signs of rabies, including Sugay and Nilsson (1966) hematophagous bats, because in Brazil the virus variant isolated in cattle is that same isolated from D. rotundus (Heinemann et al, 2002). The increase in numbers of rabies cases in hematophagous and non-hematophagous bats has been observed, as well as the number of bats that have been diagnosed in every country (Teixeira et al, 2015), possibly as a result of increased knowledge about the role of bats in cycle of rabies transmission and the greater opportunity of perception of the presence of the species in the environment altered by man.…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the difficulty of finding hematophagous bats with RABV brain infections or even with least clinical signs of rabies, including Sugay and Nilsson (1966) hematophagous bats, because in Brazil the virus variant isolated in cattle is that same isolated from D. rotundus (Heinemann et al, 2002). The increase in numbers of rabies cases in hematophagous and non-hematophagous bats has been observed, as well as the number of bats that have been diagnosed in every country (Teixeira et al, 2015), possibly as a result of increased knowledge about the role of bats in cycle of rabies transmission and the greater opportunity of perception of the presence of the species in the environment altered by man.…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 99%
“…Urbanization has been providing a variety of resources to bats, especially non-hematophagous, which have been found positive for rabies, such as plants used for afforestation by day and night shelters and other plants as food (Uieda et al 1996). Also, nocturnal public lighting of cities attract insects that are habitually consumed by several species of insectivorous bats (Teixeira et al, 2015).…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 99%
“…Research on the spatial and time distribution of rabies conducted in the states of Minas Gerais, São Paulo, and Bahia shows the influence of factors such as climate, temperature, and rainfall on the occurrence of outbreaks of rabies in certain areas (municipalities), seasons (seasonality), and throughout the years (cyclicity) (Silva et al 2001, Menezes et al 2008, Gomes et al 2011, Teixeira et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by a single-strand RNA virus of the Genus Lyssavirus, Family Rhabdoviridae (RUPPRECHT et al, 2002). In Brazil, rabies is one of the main causes of neurological syndromes in production animals like cattle and horses (RISSI et al, 2010;TEIXEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%